Key Drivers of Stakeholder Collaboration in Developing Kitesurfing Tourism in Jeneponto - Arief, Elly Isriani; Yunus, Muhammad; Syahribulan, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study explores the role of leadership, incentives, interdependence, and uncertainty in shaping stakeholder collaboration in the development of a kitesurfing tourism destination in Jeneponto District, South Sulawesi. Its aim is to understand how these key drivers influence the collaborative governance processes among local government, the private sector, and local communities. Through in-depth interviews with key stakeholders, the study identifies the significant roles of these factors in fostering effective collaboration and decision-making in tourism development. This study uses a qualitative research design and semi-structured interviews to capture the perspectives of key stakeholders involved in the development of the tourism destination. The results reveal that leadership plays a crucial role in coordinating stakeholder efforts, ensuring transparency, and facilitating decision-making. Incentives, both internal and external, motivate stakeholder participation, while interdependence among stakeholders creates mutual reliance and enhances collaboration. Finally, the research demonstrates that uncertainty, particularly regarding economic outcomes and resource allocation, can be mitigated through effective leadership and adaptive governance strategies. The findings have important implications for tourism development in rural and underdeveloped regions, emphasizing the need for inclusive, collaborative decision-making processes, the alignment of stakeholder interests, and the management of uncertainty. The study contributes to the broader understanding of collaborative governance in tourism development and provides valuable insights for future projects seeking to foster sustainable, community-driven tourism initiatives.